2021
DOI: 10.26832/24566632.2021.0602011
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical assessment of leachate from Pokhara landfill site and its impact on the quality of Seti River water, Nepal

Abstract: The management of municipal solid always poses serious environmental problems on land, air, and groundwater, especially in the case of developing countries. The characterization and assessment of leachates are necessary to understand the water quality in the urban region as well as has enormous importance in sustaining the livelihoods of people in the riverine environment maintaining the ecological balance. Landfill leachate contains thousands of complex components, which contaminate the nearby water bodies, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The value of dissolved oxygen is used to measure the extent of pollution by organic matter, demolition of the organic matter and water's self-purification. (Khanal, Adhikari, Paudel, & Adhikari, 2021). The aquatic life cannot sustain below the limit of WHO guideline which is 5 mg/L.…”
Section: Dissolved Oxygenmentioning
confidence: 99%
“…The value of dissolved oxygen is used to measure the extent of pollution by organic matter, demolition of the organic matter and water's self-purification. (Khanal, Adhikari, Paudel, & Adhikari, 2021). The aquatic life cannot sustain below the limit of WHO guideline which is 5 mg/L.…”
Section: Dissolved Oxygenmentioning
confidence: 99%
“…The study has revealed that the average waste generation per household, including plastics, paper products, rubber, and textile, is 115 gm per day. Furthermore, the disposal management of municipal solid-waste has become an issue of challenge and poses serious environmental problems such as groundwater, air, land, and the like for the government authority of developing countries (Khanal et al, 2021). This prior literature has a clear gap in the interconnection between consumer culture and solid-waste, which could create challenges in environmental issues in an urbanized city like Pokhara.…”
Section: The Issues Of Consumer Culture and Solid-wastementioning
confidence: 99%
“…Pemantauan rutin kualitas air sungai dan pengelolaan limbah yang sesuai dengan baku mutu sebelum dibuang ke badan air sangat penting untuk mempertahankan kualutas ekologis lingkungan. Informasi ilmiah terkait kualitas air lindi dan air permukaan dapat memberikan kontribusi bagi pembuat kebijakan dalam pengelolaan kualitas air dan TPA yang berkelanjutan di segmen hilir dan DAS bagian perkotaan (Khanal et al, 2021).…”
Section: Simpulanunclassified